Correction: 3D polymer objects with electronic components interconnected via conformally printed electrodes. Issue 6 (26th January 2018) - Jo, Yejin; Kim, Ju Young; Jung, Sungmook; Ahn, Bok Yeop; Lewis, Jennifer A.; Choi, Youngmin; Jeong, Sunho
Abstract : Correction for '3D polymer objects with electronic components interconnected via conformally printed electrodes' by Yejin Jo, et al., Nanoscale, 2017, 9, 14798–14803.